Socioeconomic Position, Stress, and Cortisol in Relation to Waist Circumference in African American and White Women - Baltrus, Peter T. (2010)
OBJECTIVE: Abdominal fat deposition has been shown to be related to hypertension, dyslipidemia and diabetes. Studies have shown a correlation between cortisol (a stress hormone) and abdominal fat deposition. Low socioeconomic position (SEP) has also been shown to be related to abdominal fat deposition. It is hypothesized that chronic stress associated with low SEP leads to high cortisol levels which in turn lead to abdominal fat deposition. Previous research in this area has included mainly European subjects. The purpose of this study was to examine the evidence for the SEP-chronic stress-cortisol-abdominal fat hypothesis in a sample of African American and White American women. DESIGN: Data from the Regional Assessment Health Surveillance Study (RAHSS), a survey and physical examination of a representative sample of African American and White adults residing in six counties in Georgia, were utilized. The study population included 111 African American and 119 White women. Abdominal fat deposition was measured by waist circumference (inches). Education and income were the measures of SEP. Other exposures examined included serum cortisol, self-reported daily stress level, cigarette smoking, marital status, and number of children. Associations were examined using multiple linear regression models adjusted for age and body mass index (BMI). RESULTS: Among White women, less-educated women had a waist circumference 2.22 inches larger (P<.05) than more highly educated women. Among African American women, separated or divorced women (+2.29 in, P<.05) and widowed women (+3.13 in, P<.01) had larger waist circumferences than married women. No other factors were significantly associated with waist circumference. CONCLUSIONS: The SEP-chronic stress abdominal fat accumulation hypothesis was only partially supported by the data. Different stressors and pathways may be important in producing abdominal fat accumulation in African American and White women.